The Influence of COVID-19 Pandemic on Management Earnings Forecasts - Fu, Xiangfei; Xu, Yuanze; Zhou, Fangfang; Zhao, Libin (Frontiers in Psychology, 2022)
As the biggest black swan event of 2020, the COVID-19 pandemic has significantly weakened the ability of corporate stakeholders to monitor companies on site. In this context, exploring whether the on-site supervision restrictions triggered by the COVID-19 pandemic affect management earnings forecast disclosure is crucial to protect investors' interests and promote the stable development of the capital market. Based on quarterly data of Chinese A-share listed companies’ earnings forecasts, this paper finds that: First, when the company’s headquarter city is more severely affected by the COVID-19 pandemic, the company has less willingness to disclose its management earnings forecast. And those released forecasts tend to have lower qualities. Second, higher level of media monitoring and better legal environment can mitigate the negative impacts of the COVID-19 pandemic on both the willingness and the quality of management earnings forecast disclosure. Furthermore, mediating effect analysis shows that, the reduced on-site monitoring activities that originally implemented by independent directors, institutional investors and analysts in the epidemic period greatly limit stakeholders’ monitoring efficiency, and thus cause significant influence on disclosure of management earnings forecasts.